On Conspiracy Thought Models in Thinking Climate Change - Myllylä, Mari; Delgado, José Juan Cañas; Saariluoma, Pertti (European Journal of Sustainable Development, 2023)
People make mistakes in their thinking. Errors in human thinking and incorrect information contents in people’s mental representations can be found in everyday context such as in arguments about the current climate crisis. Erroneous thinking can cause false thought models such as climate change denialism and conspiracy thinking. Therefore, it is important to analyze the information contents of incorrect schemas or thought models. This can be done with an approach called content-based psychology. In this research we analyzed 2980 public opinions posted in Finnish Social Media Platform Suomi24 to study how people think about and what kinds of illusory contents they use in constructing their representations on climate issues. We wanted to ask whether one can find illusory thinking in social media posts and to outline a typical construction of a false thought model in conspiracy thinking related to climate change. As a result, we found that conspiracy thinking can be found in online media discussions, and it is strongly associated with climate change denialism. Also, different fallacious or biased thought models have combined effects in constructing active mental representations in conspiracy thought models. Analyzing mental contents makes it possible to understand denialist and illusory thinking, but it requires further work. Keywords: Climate change thinking, Erroneous thinking, Content-based psychology, Denialism, Conspiracy thinking